An Investigation into the Estimation of a Positive Case of COVID-19: A Comparative Study between Two Phases of the Pandemic - Yasuyuki Yamaoka; Hiroko Oe (Britain International for Academic Research (BIAR-Publisher), 2021)
In Japan, the policy for polymerase chain reaction (hereafter PCR) testing changed significantly after 7 May 2020; from 4 February to 6 May, PCR testing was limited to certain patients with severe symptoms. After 7 May, the PCR test was made available to a broader range of patients due to health insurance coverage. The study aims to test whether there is a significant relationship between the conditions under which PCR tests are performed, the number of tests after 7 May, and the positive results. Using a multiple regression model, we obtained the unexpected result even if we assume that PCR testing had been carried out during 4 February to 6 May at the same level as after 7 May. The number of positive cases would have been even lower than the actual number, which we have attained. This suggests that even if PCR testing had been plentiful throughout the entire period, the number of positives that would have been captured would not necessarily have been more significant than the actual number. This estimation might suggest that the infectivity of COVID-19 varied over time. It may suggest that, over time, the infectiousness and spreading power of COVID may be transformed. Therefore, further research investigating the epidemic impact of COVID is required, which is critical for humankind.